Seed Germination and Seed Vigour Induction through Foliar Application of Plant Growth Regulators and Nutrients under Drought Stress in Chickpea (Cicer arietinum L.) - Madhana Keerthana S; R. Shiv Ramakrishnan; Sachin Nagre; Ashish Kumar; Radheshyam Sharma; Anubha Upadhyay; R. K. Samaiya (Archives of Current Research International, 2024)
Chickpea cultivation in rainfed regions, such as Madhya Pradesh, faces challenges due to water stress, impacting crop yield and quality. The study conducted assesses the impact of foliar spray with plant growth regulators and nutrients on the germination percentage, seedling length, and seed vigour indices of chickpea varieties (JG 36 and JG 14) under water deficit conditions. Cytokinin analogues, known for breaking dormancy, and other growth regulators and nutrients were applied during the flowering stage. The results revealed significant differences in germination percentage, seedling length, seed vigour index I, and seed vigour index II among irrigation levels, varieties, and foliar spray of plant growth regulators and nutrients. Under different irrigation levels, D1 (Irrigation at 30 DAS and at flower initiation) recorded the highest germination percentage (97.24%), seedling length (31.41 cm), seed vigour index I (3054.81), and seed vigour index II (52.77) compared to control D2 (Drought stress at Flowering up to physiological maturity). JG 14 (V1) performed well, achieving the highest germination percentage of 96.99%. Among the treatments, foliar application of Benzyladenine (BA) at 40 ppm (T3) resulted in the highest germination percentage (98.17%) and seed vigour index II (60.33), whereas T8 (BA 40ppm + ZnSO4 1%) exhibited the highest seedling length (31.83 cm) and seed vigour index I (3099.85). This study demonstrates that foliar spray with plant growth regulators and nutrients, particularly Benzyladenine at 40 ppm, significantly improved germination percentage, seedling length, and seed vigour index, offering potential solutions for enhancing chickpea productivity under water deficit conditions.